2015
DOI: 10.3832/ifor1397-008
|View full text |Cite
|
Sign up to set email alerts
|

Optimum light transmittance for seed germination and early seedling recruitment of Pinus koraiensis: implications for natural regeneration

Abstract: (1-2) Light transmittance regulated by canopy openness influences the microsite conditions for natural regeneration. The successful transition from seed germination to subsequent seedling recruitment (i.e., early seedling survival and growth) determines the natural regeneration potential. However, there is little information on the effect of varying light transmittance on seed germination and seedling recruitment of Pinus koraiensis Siebold & Zucc. (Korean pine). We aimed to determine the optimum light require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
2
9
0
1
Order By: Relevance
“…In this study, we demonstrated that light requirement differed between seedling emergence (including survival rate) and seedling growth. Consistent with other coniferous species, such as Pinus strobus and P. koraiensis (Parker et al 2006;Zhang et al 2014), seedling emergence and survival rate decreased with increasing light, irrespective of seed position. The highest seedling emergence and survival rate were observed at 5% and 15% sunlight, while the highest seedling growth (e.g., shoot or root morphology and biomass) occurred under 60% sunlight.…”
Section: Discussionsupporting
confidence: 81%
“…In this study, we demonstrated that light requirement differed between seedling emergence (including survival rate) and seedling growth. Consistent with other coniferous species, such as Pinus strobus and P. koraiensis (Parker et al 2006;Zhang et al 2014), seedling emergence and survival rate decreased with increasing light, irrespective of seed position. The highest seedling emergence and survival rate were observed at 5% and 15% sunlight, while the highest seedling growth (e.g., shoot or root morphology and biomass) occurred under 60% sunlight.…”
Section: Discussionsupporting
confidence: 81%
“…Korean pine (Pinus koraiensis Siebold & Zucc.) is one of the dominant tree species in forests in the cold regions of Northeast China and Siberia [1,2]. Lands dwelled by Korean pine populations account for an area of nearly five million square kilometers.…”
Section: Introductionmentioning
confidence: 99%
“…ex Ledeb. [2]. Korean pine trees in primary forests have been affected by over-harvesting for timber production and pine nuts for human consumption for four decades.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…El tratamiento con 20 0 C fue el que menos incremento en la germinación logro sobre los biotipos y nos indica que esta es la temperatura cardinal mínima y que la temperatura óptima para iniciar el proceso fisiológico de germinación y con el cual se obtuvo el mayor valor fue el de 30 0 C usada en el tratamiento PEG para los biotipos. Por ultimo al parecer las semillas de PD y MP al responder a la alternancia de temperaturas cardinales tales como 20 0 C y 30 0 C se comportan en forma independiente del régimen lumínico y presentan mecanismos enzimáticos que funcionan en diferentes temperaturas y esa respuesta se corresponde probablemente, a una adaptación a las fluctuaciones naturales del ambiente generadas por el manejo agronómico, la alternancia de las temperaturas entre el día y la noche sobre la germinación de los biotipos tal como lo hallaron en otras 71 especies 20,32 , e indicaría que sería otro método alternativo la alternancia para romper la dormancia de estos biotipos debido a la presencia de un complejo mecanismo de tipo físico, primario que está regida por los contenidos de fitohormonas, y secundaria por los factores ambientales como la luz y la temperatura 34. Luz La respuesta germinativa observada con respecto al efecto de la luz sobre PD, estuvo asociado con el fitocromo, que controla las respuestas de los cariópsides a la luz evaluando la respuesta de ITG, y que permito establecer que semillas de PD reaccionaron mejor a LR(Luz roja) y a la inducción que las de MP, los resultados que se muestran en la tabla 3 demuestran que para PD, la LR actúa sobre el mecanismo del fitocromo rompiendo la dormancia e induciendo la germinación 15,17 , e indicó que el biotipo MP es más difícil de controlar que el PD en un cultivo de arroz, es decir, los cariópsides de PD presentaron respuesta fotoblástica con mayor intensidad que MP y que la luz fue el estímulo iniciador en combinación con la acción de las fitohormonas como AG3+FAP que suplió los requerimientos del sistema de fitocromo en cariópsides de PD e indica que LR es necesaria para inducir la germinación 27 .…”
unclassified